2004
DOI: 10.1364/josab.21.001328
|View full text |Cite
|
Sign up to set email alerts
|

Theory of optical second-harmonic generation from a sphere of centrosymmetric material: small-particle limit

Abstract: The electromagnetic theory of optical second-harmonic generation from small spherical particles comprised of centrosymmetric material is presented. The interfacial region where the inversion symmetry is broken provides a source of the nonlinearity. This response is described by a general surface nonlinear susceptibility tensor for an isotropic interface. In addition, the appropriate weak bulk terms for an isotropic centrosymmetric medium are introduced. The linear optical response of the sphere and the surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
324
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(345 citation statements)
references
References 106 publications
(196 reference statements)
17
324
0
4
Order By: Relevance
“…In particular, the anisotropic nonlinear optical response, for given wavelength and incident polarization, reveals a complex contribution from all the different, nonzero, linearly independent third-order susceptibility tensor's components Rodríguez-Iglesias et al, 2009). Besides, given this anisotropy, although the nanocomposite remains being centrosymmetric, there is the possibility of measuring a nonzero optical second-order nonlinearity in the form of a second harmonic generation (SHG) signal, as it has been shown in previous results (Aktsipetrov et al, 1995;Brevet et al, 2011;Dadap et al, 1999Dadap et al, , 2004Figliozze et al, 2005;Gallet et al, 2003;Mendoza et al, 2006), and also verified by us experimentally (Rocha-Mendoza et al, 2011).…”
Section: Introductionmentioning
confidence: 62%
“…In particular, the anisotropic nonlinear optical response, for given wavelength and incident polarization, reveals a complex contribution from all the different, nonzero, linearly independent third-order susceptibility tensor's components Rodríguez-Iglesias et al, 2009). Besides, given this anisotropy, although the nanocomposite remains being centrosymmetric, there is the possibility of measuring a nonzero optical second-order nonlinearity in the form of a second harmonic generation (SHG) signal, as it has been shown in previous results (Aktsipetrov et al, 1995;Brevet et al, 2011;Dadap et al, 1999Dadap et al, , 2004Figliozze et al, 2005;Gallet et al, 2003;Mendoza et al, 2006), and also verified by us experimentally (Rocha-Mendoza et al, 2011).…”
Section: Introductionmentioning
confidence: 62%
“…Hence, it is concluded that pure and nickel nitrate doped ninhydrin crystals are also soft materials. The study of nonlinear optical conversion efficiency was carried out using the modified experimental setup of Kurtz and Perry [9,10]. A Q-switched Nd:YAG laser beam of wavelength 1064 nm, with input energy 0.701 Joule with a repetition rate of 10 Hz was used.…”
Section: Microhardness Studiesmentioning
confidence: 99%
“…10 reveals a series of even harmonics that are emitted perpendicular to the propagation direction of the incident laser beam (p S). The even harmonic radiation is created from two contributions: the Lorentz force (v × B) and the force due to the quadrupole electric field contribution [58,59]. Both terms are not accounted for in electrostatic MD codes, as can be seen from the green line in Fig.…”
Section: Microscopic Analysis Of Nonlinear Light Scatteringmentioning
confidence: 99%